The role of CO₂-EOR for the development of a CCTS infrastructure in the North Sea region: A techno-economic model and application - Roman Mendelevitch (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Scenarios of future energy systems attribute an important role to Carbon Capture, Transport, and Storage (CCTS) in achieving emission reductions. Using captured CO₂ for enhanced oil recovery (CO₂-EOR) can improve the economics of the technology. This paper examines the potential for CO₂-EOR in the North Sea region. UK oil fields are found to account for 47% of the estimated total additional recovery potential of 3739 Mbbl (1234 MtCO₂ of storage potential). Danish and Norwegian fields add 28% and 25%, respectively. Based on a comprehensive dataset, the paper develops a unique techno-economic market equilibrium model of CO₂ supply from emission sources and CO₂ demand from CO₂-EOR to assess implications for a future CCTS infrastructure. The demand for fresh CO₂ for CO₂-EOR operation is represented by an exponential storage cost function. In all scenarios of varying CO₂ and crude oil price paths the assumed CO₂-EOR potential is fully exploited. CO₂-EOR does add value to CCTS operations but the potential is very limited and does not automatically induce long term CCTS activity. If CO₂ prices stay low, little further use of CCTS can be expected after 2035.
Keywords: C61; L71; O33; 330; CO2-EOR; CCTS; complementarity modeling; CO2 transport